2016
DOI: 10.1590/1678-98652016000600007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the presence of nutrient claims on labels of ultra-processed foods directed at children and of the perception of kids on such claims

Abstract: Objective: To characterize the presence of nutrient claims on the front-of-pack labels of ultra-processed foods directed at children and gain insight on children' views about the presence of marketing strategies and nutrient claims on labels of ultra-processed foods. Methods: Analysis of images (front panel, nutrition facts table, and ingredients list) of labels from 535 packaged foods with marketing strategies directed at children obtained in an audit-type survey conducted at a Brazilian large supermarket sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 16 publications
(15 reference statements)
0
18
0
2
Order By: Relevance
“…Twenty-five studies inquired several topics related with television advertisement. Fourteen of them found that food and nonalcoholic beverage advertisements represented between 5.6% and 36.4% of all television ads 24,[27][28][29]34,36,37,40,43,49,52,53,56,59 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-five studies inquired several topics related with television advertisement. Fourteen of them found that food and nonalcoholic beverage advertisements represented between 5.6% and 36.4% of all television ads 24,[27][28][29]34,36,37,40,43,49,52,53,56,59 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies also found that more food advertisements appear during children' s programming compared with general audience programming and that child-oriented advertisements had less nutritional quality compared with general audience advertisements 24,28,40,43,52,56,57 .…”
Section: Continuementioning
confidence: 99%
See 3 more Smart Citations